2009
DOI: 10.1159/000250441
|View full text |Cite
|
Sign up to set email alerts
|

Oral Challenge with Pasteurized Egg White from <i>Gallus domesticus</i>

Abstract: Background: Since raw egg may cause digestive toxic infections, we assessed whether pasteurized raw egg white is as reliable as fresh raw egg white in the diagnosis of egg allergy. Methods: Thirty-two egg-allergic children were challenged with both pasteurized and fresh raw egg white. Open challenges were carried out with increasing doses of pasteurized raw egg white and fresh raw egg white administered every 60 min. Results: Eleven children (34.4%) had positive challenges with pasteurized raw egg white. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
4
16
0
1
Order By: Relevance
“…Our results are consistent with those of Jurado‐Palomo et al. who found no allergenic differences in vitro or in vivo between raw and pasteurized egg white. The present study also showed that the second heat treatment after pasteurization to obtain DEW – drying with air at 80°C for 1 min – does not affect the allergenicity of the proteins.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with those of Jurado‐Palomo et al. who found no allergenic differences in vitro or in vivo between raw and pasteurized egg white. The present study also showed that the second heat treatment after pasteurization to obtain DEW – drying with air at 80°C for 1 min – does not affect the allergenicity of the proteins.…”
Section: Discussionsupporting
confidence: 93%
“…PEW (Guillen, Valencia, Spain), whose allergenicity has been proven equivalent to raw EW , was the material used for the OIT (Supporting Information Table in the repository), which was performed in three phases. (a) The initial dose escalation phase performed in the hospital, starting with 1 mL of a 1/1000 water solution of PEW; if the patient did not develop allergic symptoms, a double dose was administered every 30 minutes until reaching undiluted PEW; if the patient did not develop DARs, they were discharged 2 hours later and the desensitization protocol was continued the next day.…”
Section: Methodssupporting
confidence: 86%
“…Care must however be taken relating to potential risk of infection that could be avoided using pasteurized fractions or extracts, provided they are not cross contaminated and correctly standardized. No impact of pasteurization on egg allergenicity, as generally assumed, was confirmed on E and EW for most but not all tested children. This might be related to protein unfolding and/or aggregation, which occur during pasteurization .…”
Section: Discussionmentioning
confidence: 99%
“…Oral challenges, one performed with raw/pasteurized EW or E and the other with hard‐boiled EW or baked egg, establish the phenotype. The use of pasteurized products to avoid potential risk of infection is supported by studies reporting that they maintained their IgE‐binding capacity or allergenicity . Baked egg‐reactive subjects have larger skin prick test (SPT) wheals and greater EW‐, OVA‐ and OVM‐specific IgE levels than baked egg‐tolerant subjects but with a great deal of overlap .…”
Section: Introductionmentioning
confidence: 99%